Workshop Pengembangan Budaya Sekolah Bernilai Qurani sebagai Upaya Penguatan Karakter Peserta Didik - Septian Arief Budiman; Nurjaya Nurjaya; Fil Isnaeni (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2026)
School culture plays a crucial role in shaping students' character and behavior. However, the implementation of Qur’anic values within school culture remains a challenge due to limited understanding among educators and the lack of systematic integration of Islamic values into daily school activities. This community service program aimed to enhance teachers’ knowledge and skills in developing a Qur’anic-based school culture through a workshop. The $ employed participatory methods, including lectures, group discussions, case studies, and action plan development. The participants consisted of teachers and educational staff from the partner school. The workshop materials focused on the concept of school culture, the integration of Qur’anic values in educational settings, and strategies for fostering a religious and character-oriented school environment. The results indicated a significant improvement in participants’ understanding of Qur’anic-based school culture and their ability to design practical programs for implementation in schools. Several follow-up initiatives were developed, including Qur’an reading habituation, congregational prayer programs, Islamic character-building activities, and social care programs. The workshop contributed positively to strengthening teachers’ capacity to cultivate a school environment that promotes religious values, discipline, responsibility, honesty, and social awareness. Therefore, this program can serve as an effective model for supporting character education through the development of a Qur’anic-based school culture.